Outcome analysis of the Gore Conformable Thoracic Stent Graft with active control system for the treatment of arch and descending thoracic aortic disease - Böckler, Dittmar; Bischoff, Moritz; Kronsteiner, Dorothea; Skrypnik, Denis; Meisenbacher, Katrin (European journal of cardio-thoracic surgery, 2021)
Over the past 3 decades, thoracic endovascular aortic repair (TEVAR) has evolved as the treatment modality of choice for various pathologies of the thoracic aor